1995
DOI: 10.1074/jbc.270.27.15974
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus B18R Gene Encodes a Type I Interferon-binding Protein That Blocks Interferon α Transmembrane Signaling

Abstract: Poxviruses encode a large number of proteins that attenuate the inflammatory and immune responses to infection. In this report we demonstrate that a number of orthopoxviruses express a type I interferon (IFN)-binding protein, which is encoded by the B18R open reading frame in the WR strain of vaccinia virus. The B18R protein has significant regions of homology with the alpha subunits of the mouse, human, and bovine type I IFN receptors, bound human IFN alpha 2 with high affinity, and inhibited transmembrane si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
212
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(216 citation statements)
references
References 43 publications
4
212
0
Order By: Relevance
“…Type I IFN neutralization was performed with B18R, a soluble type I IFN receptor derived from the Western Reserve strain of vaccinia virus. B18R is reported to bind and/or inhibit the activity of all human type I IFNs tested thus far, including IFN␣1, IFN␣2, IFN␣7, IFN␣8, IFN , and IFN␤, but not human type II IFN (IFN␥) (24)(25)(26). We have found that B18R potently inhibits type I IFN-induced human PBMC responses (van Seventer J, Nagai T, Mangini A: unpublished observations).…”
Section: Induction Of Siglec-1 Expression In Vitro Onmentioning
confidence: 87%
“…Type I IFN neutralization was performed with B18R, a soluble type I IFN receptor derived from the Western Reserve strain of vaccinia virus. B18R is reported to bind and/or inhibit the activity of all human type I IFNs tested thus far, including IFN␣1, IFN␣2, IFN␣7, IFN␣8, IFN , and IFN␤, but not human type II IFN (IFN␥) (24)(25)(26). We have found that B18R potently inhibits type I IFN-induced human PBMC responses (van Seventer J, Nagai T, Mangini A: unpublished observations).…”
Section: Induction Of Siglec-1 Expression In Vitro Onmentioning
confidence: 87%
“…We selected immunoblotting with antiphosphotyrosine antibodies because the transiently overexpressed Jak kinases are baseline tyrosine phosphorylated [5,8,10,25] allowing us to discriminate the recombinant protein from the non-phosphorylated endogenous kinases. More over, tyrosine phosphorylation of the endogenous Jak kinases resulting from type I IFNs in the conditioned medium of vaccinia virus infected cells is not possible, as vaccinia virus produces the B 18R protein that binds IFNs and completely blocks IFNc~ signaling [26]. Fig.…”
Section: Interaction Between Jak-1 and Tyk-2mentioning
confidence: 99%
“…The cDNAs encoding the wild type Jak-1 and Tyk-2 tyrosine kinases and the kinase deficient mutant Tyk-2(K930I) were subcloned into the pGem vector under the control of the T7 promoter [24]. No IFN~ treatment was performed in the vaccinia virus experiments because vaccinia virus blocks binding and signaling through the type I IFN-R [26]. A weak tyrosine phosphorylated band observed in anti-Tyk-2 immunoprecipitates after transfection with Tyk-2(K930I) does not correspond to Tyk-2 since it is not detected in anti-Tyk-2 immunoblots (data not shown).…”
Section: Homodimerization Of Tyk-2mentioning
confidence: 99%
“…The sequence of M135R is similar to that of the vaccinia virus B18R, an IFN-␣/␤ receptor mimic (2,4,10,25). Therefore, we next tested the ability of M135R to bind rabbit type I IFN.…”
Section: M135r Is Nonessential For MV Replication In Vitromentioning
confidence: 99%
“…MV also encodes a secreted inhibitor of TNF (M-T2) that can block the ability of rabbit TNF to bind to its cognate cell surface TNF receptors. Other poxvirus genera have acquired other strategies; for instance, the yatapoxviruses encode a high-affinity TNF binding protein (2L) (8,22), while the orthopoxviruses encode extracellular inhibitors, including several TNF binding proteins (Crm family [21], viral IFN-␥Rs [B8R family], and vIFN-␣/␤-R [B18R] [3,10,25]). Many poxviruses also encode multiple intracellular inhibitors which include homologs of vaccinia virus E3L, which inhibits the ␣ subunit of eukaryotic initiation factor 2, and K3L, an inhibitor of protein kinase R (1,4,24).…”
Section: Myxoma Virus (Mv) Is a Rabbit-specific Virus That Causes A Lmentioning
confidence: 99%